Reducing vulnerability and precarity of low-skilled women in short-term migration from the global south: Key recommendations for the G-20 - Wu, Joyce; Kilby, Patrick; Abdulrahim, Sawsan; Choudhury, Zahid ul Arefin; Ratna, Nazmun; ElDidi, Hagar; Ringler, Claudia (T20 Italy, 2021)
Women migrant workers make significant contributions to the global economy, but face risks of being subject to forced labour and trafficking, heightened by COVID-19. As women migrate from low-income to G20 countries to undertake key service functions, the G20 should uphold women’s human rights and fair work conditions. G20 countries can support migrant women workers through technical and information exchange, giving voice, and partnership with source countries to certify migration agents, provide social assistance and establish reintegration programmes. G20 can also support migrants in their own countries by providing standard employment contracts, securing access to health services and ensuring accessible redress mechanisms.